The association between nicotine dependence and smoking practices among Malay male smokers working in Selangor municipalities - A. F., Ahmad Farhan; I., Suriani; A. R., Hejar; Z. Abidin, E.; Saliluddin, S. M. (Community Health Society Malaysia, 2015)
Introduction: Nicotine dependence develops over time. It radically contributes to adverse health effects and influences smoking cessation. Globally the prevalence of current nicotine dependence has been reported as being between 46 to 53 percent. Nicotine dependence is associated with many factors, one of which is smoking practices.